A fast optimal load shedding method for power system reliability assessment based on shadow price theory. (April 2022) - Hou, Kai; Tang, Puting; Liu, Zeyu; Jia, Hongjie; Yuan, Kai; Sun, Chongbo; Song, Yi
Abstract: The optimal load shedding calculations of an enormous number of contingency states are the most challenging impediments for power system reliability assessment, especially in a large-scale system with multiple types of loads. To deal with that, this paper proposes a fast method that accelerates the calculation of optimal load shedding based on the shadow price. This method calculates the optimal load shedding of systems by shadow-price-based linear functions, rather than the time-consuming OPF algorithms. The hundred percentage criterion is used to look for the matching shadow price of states. Case studies are performed on the RTS-79 system. The results show that the proposed methodology can significantly simplify the solving process and reduce the calculation time.